Antithrombotics in atrial fibrillation and coronary disease. (August 2014) - Velagapudi, Poonam; Turagam, Mohit K; Agrawal, Harsh; Mittal, Mayank; Kocheril, Abraham G; Aggarwal, Kul
<x xml:space="preserve">Abstract</x> Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia and approximately 18–45% of AF patients have concomitant coronary artery disease (CAD). Several studies have demonstrated that oral anticoagulation is the mainstay of therapy for stroke prevention in AF. Similarly, antiplatelet therapy including aspirin and P2Y12 inhibitor is recommended in the management of acute coronary syndrome and stable CAD. Despite the high prevalence of CAD with AF, practice guidelines are scarce on the appropriate antithrombotic regimen due to lack of large-scale randomized clinical trials. The use of direct thrombin and factor Xa inhibitors for stroke prevention in AF has also complicated the possible combinations of antithrombotic therapies. This review aims to discuss the available evidence regarding aspirin as an antithrombotic strategy, the role of novel anticoagulants and the specific clinical situations where aspirin may be beneficial in patients with AF and CAD.